1997
DOI: 10.1105/tpc.9.8.1339
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen assimilation in alfalfa: isolation and characterization of an asparagine synthetase gene showing enhanced expression in root nodules and dark-adapted leaves.

Abstract: Asparagine, the primary assimilation product from N2 fixation in temperate legumes and the predominant nitrogen transport product in many plant species, is synthesized via asparagine synthetase (AS; EC 6.3.5.4). Here, we report the isolation and characterization of a cDNA and a gene encoding the nodule-enhanced form of AS from alfalfa. The AS gene is comprised of 13 exons separated by 12 introns. The 5' flanking region of the AS gene confers nodule-enhanced reporter gene activity in transformed alfalfa. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 60 publications
4
58
0
10
Order By: Relevance
“…The relatively modest increase in free ammonium in nodules of the transformed plants in comparison with the decrease in GS activity and the fact that biological N 2 fixation releasing a constant flux of ammonium was not affected also support this hypothesis. This hypothesis also fits well with the finding that AS expression in the nodules is independent of nitrogenase activity (Shi et al, 1997). In a recent study, an increase in Asn also has been observed in leaves when photorespiratory ammonium is accumulating as the result of impaired GOGAT activity, suggesting that alternative metabolic pathways may be activated to avoid ammonium accumulation (Ferrario-Méry et al, 2002).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The relatively modest increase in free ammonium in nodules of the transformed plants in comparison with the decrease in GS activity and the fact that biological N 2 fixation releasing a constant flux of ammonium was not affected also support this hypothesis. This hypothesis also fits well with the finding that AS expression in the nodules is independent of nitrogenase activity (Shi et al, 1997). In a recent study, an increase in Asn also has been observed in leaves when photorespiratory ammonium is accumulating as the result of impaired GOGAT activity, suggesting that alternative metabolic pathways may be activated to avoid ammonium accumulation (Ferrario-Méry et al, 2002).…”
Section: Discussionsupporting
confidence: 74%
“…AS protein was detected with the antibodies raised against the nodule enzyme from alfalfa (Medicago sativa; Shi et al, 1997). Proteins were visualized using peroxidaseconjugated goat anti-rabbit antibodies (Towbin et al, 1979).…”
Section: Protein Extraction Fractionation Enzymatic Assay and Westmentioning
confidence: 99%
“…However, the levels of gene expression for the cytosolic GS1 are not significantly affected by light (37). In contrast to the situation with GS2, light was found to repress accumulation of AS1 mRNA levels in a variety of plants including Arabidopsis, Pisum, Medicago, Glycine, Triphysaria, and Phaseolus (24,26,(28)(29)(30)32). The negative effect of light on AS gene expression was also shown to be mediated, at least in part, by phytochrome in Arabidopsis and pea (30,32).…”
Section: Light and Metabolic Regulation Of Genes Involved In Nitrogenmentioning
confidence: 80%
“…Finally, in most temperate legumes the assimilated Gln is exported out of the nodule, principally as Asn, which requires the concerted activity of a Gln-dependent Asn synthetase and Asp aminotransferase. In alfalfa, there is a nodule-enhanced Gln-dependent Asn synthetase (Shi et al, 1997) and in L. corniculatus and alfalfa there are nodule-enhanced Asp aminotransferases (P2 and AAT2, respectively), which at least in alfalfa has been located in a plastid Mett et al, 1996). In indeterminate V. faba nodules most infected cells do not make contact with uninfected cells and it has been proposed that amino acids are released by infected cells into the apoplast from which they can be actively accumulated by uninfected cells (Peiter et al, 2004).…”
mentioning
confidence: 99%